The Arabidopsis RING‐Type E3 Ligase TEAR4 Controls Seed Germination by Targeting RGA for Degradation - Hao Yu; Yutao Wang; Yi Wang; Xing Wang Deng; Genji Qin (Advanced Science)
Abstract Light and DELLA proteins are central factors controlling seed germination which is critical for seed plant survival and agricultural production. However, the mechanisms underlying DELLA degradation under different light conditions during seed germination remain to be clarified. Here, it is reported that TIE1‐ASSOCIATED RING‐TYPE E3 LIGASE4 (TEAR4) and other TEARs redundantly promote DELLA degradation to positively regulate seed germination in Arabidopsis. The tear1/2/3/4/5/6 sextuple mutant displayed delayed seed germination under the white or PhyB‐dependent light condition, and nearly no seed germination under the PhyA‐dependent light condition. The DELLA protein REPRESSOR OF ga1‐3 (RGA) accumulated in tear1/2/3/4/5/6, and disruption of RGA and GA‐INSENSITIVE (GAI) in tear1/2/3/4/5/6 rescued defective seed germination. Far‐red (FR) light rapidly induced TEARs, and TEAR4 is shown to act as an E3 ligase. It is showed that both GA‐dependent and TEAR‐mediated DELLA degradation pathways are indispensable for PhyA‐dependent germination. It is found that TEAR homologs PpTEAR1 and PpTEAR2 from the moss Physcomitrium patens interacted with Arabidopsis DELLAs to promote their degradation, and overexpression of PpTEAR1 or PpTEAR2 completely rescued defective PhyA‐dependent seed germination in phya‐211. This findings demonstrate that TEARs act as critical players in fine‐tuning seed germination, and TEAR‐mediated DELLA degradation might be an ancient pathway conserved in plant kingdom.